The bacterial profile and antibiotic susceptibility in skin and soft tissue infections at tertiary care hospital of Quetta, Pakistan - Aman, Bibi Sazain; Taj, Muhammad Kamran; Taj, Imran; Azam, Saima; Khan, Sakina; Rashid, Rozina (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the bacterial profile and antibiotic susceptibility in skin and soft tissue infections among patients in a tertiary care setting. Method: The cross-sectional cohort study was conducted at the Centre for Advanced Studies in Vaccinology and Biotechnology, University of Balochistan, Quetta, Pakistan, from June 2021 to May 2022, and comprised bacteria-infected skin samples that were collected from the Bolan Medical Complex Hospital, Quetta, and the Sandeman Provincial Hospital, Quetta. The swab samples were immediately cultured, and positive samples were evaluated for biochemical tests, antibiotic susceptibility test and polymerase chain reaction. Data was analysed using SPSS 22. Results: Of the 800 samples, 598(74.7%) tested positive for pathogenic bacteria. Staphylococcus aureus accounted for 316(39.5%) infections, followed by clostridium perfringens 18.96(2.37%), escherichia coli 120(15.12%), pseudomonas aeruginosa 98(12.25%) and klebsiella pneumoniae 44(5.5%). Among all the infected samples, 380(47.5%) belonged to males, 218(27.25%) to patients aged 5-20 years, 448(56%) to the uneducated subjects, and 462(57.87%) to patients having lower socioeconomic status. Pseudomonas aeruginosa showed the highest level of resistance against all antibiotics. Conclusion: Regular surveillance and proper use of antibiotics should be encouraged in hospitals to limit the spread of antibiotic resistance against pathogenic bacteria. Key Words: Antibiotics, Bacteria, Surveillance, Frequency, Skin.